2021
DOI: 10.3390/rs13122339
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Above-Ground Biomass of Potato Using Random Forest and Optimized Hyperspectral Indices

Abstract: Spectral indices rarely show consistency in estimating crop traits across growth stages; thus, it is critical to simultaneously evaluate a group of spectral variables and select the most informative spectral indices for retrieving crop traits. The objective of this study was to explore the optimal spectral predictors for above-ground biomass (AGB) by applying Random Forest (RF) on three types of spectral predictors: the full spectrum, published spectral indices (Pub-SIs), and optimized spectral indices (Opt-SI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 73 publications
2
38
0
Order By: Relevance
“…This may explain why the coupling of NWIs-3b with the three models showed a better performance in the estimation of the three plant traits in both calibration and validation datasets as compared with the other types of SRIs. Similarly, Yang et al [41] reported that the type of SRIs significantly influenced the performance of RF models for estimating the AGB of potato crops across different growth stages.…”
Section: Performance Of Different Models To Predict the Measured Traitsmentioning
confidence: 95%
See 3 more Smart Citations
“…This may explain why the coupling of NWIs-3b with the three models showed a better performance in the estimation of the three plant traits in both calibration and validation datasets as compared with the other types of SRIs. Similarly, Yang et al [41] reported that the type of SRIs significantly influenced the performance of RF models for estimating the AGB of potato crops across different growth stages.…”
Section: Performance Of Different Models To Predict the Measured Traitsmentioning
confidence: 95%
“…This is because the combined few wavelengths in specific formulas increase the sensitivity of SRIs to different vegetation physical and biochemical proprieties rather than the target traits [70,77,83,84]. Therefore, recent studies have demonstrated that the SRIs coupled with the development of data-driven models, such as RF or multivariate regression models such as PLSR and MIR, can improve the accurate estimation of plant traits as compared to the usage of individual SRIs [41,48,50,52,84,85]. However, the numbers and types of input variables in these models can significantly influence their performance in estimating the plant traits.…”
Section: Performance Of Different Models To Predict the Measured Traitsmentioning
confidence: 99%
See 2 more Smart Citations
“…In general, the performance of SRIs in the estimation of various plant traits is often inconsistent when measured across genotypes, years, sites, and phenological stages, as almost all of them include only two to three wavelengths [ 40 , 41 , 42 , 43 ]. Additionally, because the Chl content and LAI have similar influences on the spectral reflectance of the canopy, particularly at the wavelengths of 550 and 750 nm, these limited wavelengths influence the performance of SRIs when they are used individually to uncouple the combined effect of both traits [ 33 ].…”
Section: Introductionmentioning
confidence: 99%